Characterization of Mice Ubiquitously Overexpressing Human 15-Lipoxygenase-1: Effect of Diabetes on Peripheral Neuropathy and Treatment with Menhaden Oil. (16th March 2021) - Coppey, Lawrence; Obrosov, Alexander; Shevalye, Hanna; Davidson, Eric; Paradee, William; Yorek, Mark A.
Abstract : To rigorously explore the role of omega-3 polyunsaturated fatty acids (PUFA) in the treatment of diabetic peripheral neuropathy (DPN), we have created a transgenic mouse utilizing a Cre-lox promoter to control overexpression of human 15-lipoxygenase-1 (15-LOX-1). In this study, we sought to determine the effect of treating type 2 diabetic wild-type mice and transgenic mice ubiquitously overexpressing 15-LOX-1 with menhaden oil on endpoints related to DPN. Wild-type and transgenic mice on a C57Bl/6J background were divided into three groups. Two of each of these groups were used to create a high-fat diet/streptozotocin model for type 2 diabetes. The remaining mice were control groups. Four weeks later, one set of diabetic mice from each group was treated with menhaden oil for twelve weeks and then evaluated using DPN-related endpoints. Studies were also performed using dorsal root ganglion neurons isolated from wild-type and transgenic mice. Wild-type and transgenic diabetic mice developed DPN as determined by slowing of nerve conduction velocity, decreased sensory nerve fibers in the skin and cornea, and impairment of thermal and mechanical sensitivity of the hindpaw compared to their respective control mice. Although not significant, there was a trend for the severity of these DPN-related deficits to be less in the diabetic transgenic mice compared to the diabetic wild-type mice. Treating diabetic wild-type and transgenic mice with menhaden oil improved the DPN-related endpoints with a trend for greater improvement or protection by menhaden oil observed in the diabetic transgenic mice. Treating dorsal root ganglion neurons with docosahexanoic acid but not eicosapentaenoic acid significantly increased neurite outgrowth with greater efficacy observed with neurons isolated from transgenic mice. Targeting pathways that will increase the production of the anti-inflammatory metabolites of omega-3 PUFA may be an efficacious approach to developing an effective treatment for DPN.